Geographic Information System of Potential Tsunami Impact Areas and Safe Gathering Places for Coastal Tourism Area in Badung Regency, Bali Province - Suyadnya, I Made Arsa; Khrisne, Duman Care (Journal of Electrical, Electronics and Informatics, 2017)
The Southern part of Bali especially Badung regency, in addition to having natural beauty and popular tourist attraction, it has a high potential for disaster. The fact is the coastline of Bali in the south is prone to tsunami because Bali is located close to the colliding zone between the Indo-Australian plate and the Eurasia plate, which presents the main source of the local tsunami that could hit the island of Bali. This research undertakes the design and development of a Geographic Information System (GIS) that can provide information and socialization of potential tsunami impact areas and safe gathering places for coastal tourism area in Badung regency. This application is built web-based by using Google Maps API v3. In this Geographic Information System, users can identify potential tsunami impact areas, obtain information on evacuation methods in the event of a tsunami disaster and can find the nearest safe gathering places to do an evacuation. By utilizing geolocation and direction services from Google Maps API v3, simulation of the nearest evacuation route has been successfully built. Evacuation is done by considering two possible evacuation sites. The first possibility is to evacuate to the nearest vertical high building, and the second evacuation site is away from the danger zone (red zone) and towards the safe zone (yellow zone or outside the yellow zone).